ANALISIS JARINGAN KOMUNIKASI HOLYWINGS PADA PROMOSI MUHAMMAD-MARIA DI TWITTER - Dwi Setyo Aji; Irwan Dwi Arianto (Jurnal Pustaka Komunikasi, 2023)
This study is aim for map communication network formed when Holywings company got Public Relation Crisis during their product campaign using Muhammad Maria in Social Media Twitter. This issue have been considered by community as a religious blasphemy. This research aim to determine actors who control the information in this issue which lead actors can influence audience’s sentiment in the issue itself. This actors will create a cluster who will affect Holywings corporate image in Public Relations theory. Researchers used a quantitative research methods with a descriptive approach in conducting this research. This research use NodeXL as software for data mining and data analysis for find metrics and actors inside the network. This method used since conversation in internet era cannot analyzed in tradisional technique. Based on analysis that has been done there are 3 main actors @imanlagi, @catchmeupid dan @knpiharis. In communication network there are 3 main clusters created.